Tomini Gulf Maritime Axis in International Law Review - Towadi, Mellisa; Mandjo, Julius T (Universitas Negeri Semarang, 2021)
This article is based on the concept of a maritime axis based on several issue points in the Tomini Gulf area, researched to map issues based on a review of International Law. The article focuses on the existing conditions of the tomini bay area in its management and protection but at the level of the maritime sector that is related to the issue of security defense of the gulf tomini waters. Based on normative juridical methods, the article explains that the gulf of tomini which is semi-enclosed water, still requires significant support from the executive elements, especially in terms of regional cooperation and international cooperation in the fields of economy, defence and security. This is concerned with the territorial and EEZ regions that simultaneously border the Pacific Ocean and the development of the Gulf of Tomini from the aspect of prosperity and security. Moreover, the state does not have to refer to only one international intrusion. However, maritime synergy is needed in all aspects of the tomini bay waters, be it from environmental, utilization and socio-cultural economy. Some specifically regulated international conventions need a more profound review to implement a targeted management system and definite legal protection at the regional level.